(untitled) (Journal of Pakistan Orthopaedic Association, 2024)
Objective: The purpose of current study is the comparison of the radiological outcome of open reduction in children with unilateral vs bilateral DDH following staged surgery. Methods: In current study, the medical records of 53 children were retrospectively analyzed, out of which 18 children were with bilateral dysplasia (36 hips) and 35 children were with unilateral dysplasia of hip, all children were treated via staged open reduction with pelvic & femoral osteotomies, operated at Ghurki Trust Teaching Hospital Lahore between August 2020 to July 2022 after taking ethical approval from Hospital Ethical Committee. Patients were followed up to measure the radiological outcome in terms of presence of AVN, subluxation and redislocation of the hip joint. Kalamchi and MacEwen classification and Severin’s criteria were used to measure the outcome. Data were entered and analyzed using SPSS software version 27 taking p-value?.05 as statistically significant. Results: A total of 53 DDH patients between the ages of 1 to 5yrs underwent open reduction with pelvic and femoral osteotomies. Among these, 35(66.0%) had unilateral DDH, while 18(34.0%) had bilateral DDH. In the bilateral DDH group, the average age of patients at the time of surgery was 3.7yrs while in the unilateral DDH group, it was 3.3 years. More than half of cases 12(66.7%) reported type II or worse AVN as per the classification of Kalamchi and MacEwen in the bilateral group, while less than half 12(34.3%) reported type II or worse AVN in the unilateral group. Radiological evaluation using Severin’s criteria revealed that normal appearance was found in 9(50.0%) bilateral and 21(60.0%) unilateral cases. There is statistically significant difference found in radiological outcome between Unilateral and Bilateral DDH groups. Conclusion: The rate of femoral head osteonecrosis in bilateral DDH patients treated with open reduction is greater than that in unilateral DDH patients at the same hospital having been treated with similar protocols. In the current study, as per the Severin’s classification, the radiographic outcome was significantly better in the unilateral hip dysplasia group.